Pengaruh ROA dan DER Terhadap Stock Price Perusahaan yang Terdaftar di BEI - Zulkarnain Zulkarnain; Regina Syahara; Yuli Novitasari (Cakrawala Repositori IMWI, 2020)
The aim of this study to determine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Stock Price of the food and beverage subsector manufacturing companies listed on Indonesia Stock Exchange in 2013-2017. Population of this study are 18 companies. Sample selection is done by using purposive sampling method to obtain 12 companies. Data used in this study is secondary data obtained from the company’s annual report. The data analysis technique used was multiple linear regression with SPSS version 25. The results showed that ROA had a positive-significant effect on Stock Price. DER on the other hand has no effect on Stock Price. Simultaneously, ROA and DER have a significant effect on Stock Price of the food and beverage subsector manufacturing companies for 2013-2017.